Development and exacerbation of pulmonary nontuberculous mycobacterial infection in patients with systemic autoimmune rheumatic diseases. Issue 3 (3rd May 2020) - Takenaka, Sayaka; Ogura, Takehisa; Oshima, Hisaji; Izumi, Keisuke; Hirata, Ayako; Ito, Hideki; Mizushina, Kennosuke; Inoue, Yuki; Katagiri, Takaharu; Hayashi, Norihide; Kameda, Hideto
Abstract: Objectives: To examine the development and exacerbation of pulmonary nontuberculous mycobacterial (NTM) infection in patients with systemic autoimmune rheumatic diseases (SARD). Methods: We conducted a case–control study. Seventeen of 7013 patients with SARD fulfilling the criteria for pulmonary NTM infection were enrolled in the NTM group. The control group was matched for age, sex, and SARD at a ratio of 2:1. Results: Eight patients with rheumatoid arthritis, four with systemic vasculitis, three with Sjögren's syndrome, and one each with dermatomyositis and systemic lupus erythematosus were included in the NTM group. Mycobacterium avium was detected in 12 (71%) patients, M. chelonae in 2, and M. intracellulare, M. abscessus, and M. kansasii in 1 patient each. Preexisting lung disease was more common in the NTM group than in the control group (88% versus 38%, p  = .0009), particularly bronchiectasis (65% versus 29%, p  = .033). The body mass index and serum albumin level were significantly lower in the NTM group than in the control group. Six patients (35%) experienced NTM exacerbation during observation. Clinical immune status at the time of NTM diagnosis, as indicated by the peripheral blood leukocyte/lymphocyte count and serum immunoglobulin G level, was unremarkable and comparable between patients with and without exacerbation, as were the treatments for SARD. Conclusions: In patients with SARD, pulmonary NTM infection may develop and exacerbate without clinically apparent immunosuppression.